A Review On Cloud Data Security With MHT Based Integrity Authentication Framework - Sajjan, RS; Vijay R, Ghorpade; Arkas, BD (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing that concern the latest trend in application development for Internet services, relying on clouds of servers to manage multiple tasks that used by individual machines. So without the Internet Cloud is not for the use. The developers initiates special services, such as email, calendars, and word processing, and host them entirely online, also processing of different applications proposed by the cloud of special servers with cloud computing. Cloud storage for storing and sharing data across multiple users become more popular. Cloud computing is innovative trend that supposed to do data storing at data centres. But the limitations of cloud data security don’t prescribe cloud better. To improve data reliability and availability, cloud service providers mature strategies such as storing multiple replicas along with original datasets. Public data auditing schemes enable the users to verify their outsourced data storage without retrieving the whole dataset. Due to the efficiency and security problems the system communication overhead (bandwidth) didn’t maintains data integrity, and public auditing. The on-demand service provision with utilization of limited resources of client system benefits the client. However, data outsourcing paradigm in cloud is one of the biggest security concerns. Frequent integrity checking is needed to keep an eye on data. The proposed scheme makes use of Merkle Hash Tree (MHT) and AES algorithm to ensure data integrity at the unsecured server.